PKM meningkatkan kemampuan guru dalam mengoperasikan perangkat lunak Wolfram Alpha - Fajar Arwadi; Muharram Muharram; Ahmad Fudhail Majid (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The main objective of this Community Partnership Program (PKM) was increasing the competency of teachers in making computation using a software. It was aimed at simplifying the teachers to verify the answers of problems related to the topic they teach in classroom. It stemmed from the problems, namely, the instructor for the software was still limited and the softwares commonly they used were not practical. It caused the incompetency of the teacher in operating a software, i.e. Wolfram Alpha for computation. Therefore, it is necessary to make a training program that can facilitate the teachers in operating Wolfram Alpha software. Specifically, the activity can develop the ability of the teachers in making computation for solving problems in mathematics and natural science. The outcomes of the program are that the participants were enthusiastic to the activity given. They frequently consult to the instructor when there are some problems occurring in the training related to Wolfram Alpha. Finally, the teachers are able to make computation using software.